2018
DOI: 10.1002/app.46629
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of starch/poly(butylene adipate‐co‐terephthalate) blown films using itaconic acid and sodium hypophosphite

Abstract: Itaconic acid (IA) has potential as a compatibilizing agent in polymeric blends due to its unique chemical characteristics. Sodium hypophosphite (SHP) has been studied as a catalyst in esterifying reactions using multicarboxylic acids. Starch/poly(butylene adipate‐co‐terephthalate) blown films containing IA, with and without SHP, were produced. The film containing IA presented higher tensile strength (8.166 MPa) and elongation (891.473%) than the control film (5.548 MPa and 487.637%, respectively). When SHP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, the presence of grape seed oil in the matrix helps the TPS and PBAT polymer matrices to mix homogeneously with each other, thus increasing the strength of the composite material. Studies have shown that because of the hydrophobic nature of PBAT, the heterogeneous appearance issue in TPS/PBAT blends is also observed 25,26 . However, using molecules that act as compatibilizers between two different phases is considered an advantage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of grape seed oil in the matrix helps the TPS and PBAT polymer matrices to mix homogeneously with each other, thus increasing the strength of the composite material. Studies have shown that because of the hydrophobic nature of PBAT, the heterogeneous appearance issue in TPS/PBAT blends is also observed 25,26 . However, using molecules that act as compatibilizers between two different phases is considered an advantage.…”
Section: Resultsmentioning
confidence: 99%
“…The H P H of SHP could react with >C═C< of unsaturated carboxylic acid and the phophinate group could be introduced into the product's structure. [25][26][27][28][29] However, the usage of SHP to synthesize PCE is scarcely reported and it is promising to explore this method in the preparation of PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypophosphite (SHP) is a common industrial chemical and widely used as a hypophosphite group‐containing reactant in the fields of cotton garments and circulating water system. The HPH of SHP could react with >C═C< of unsaturated carboxylic acid and the phophinate group could be introduced into the product's structure 25–29 . However, the usage of SHP to synthesize PCE is scarcely reported and it is promising to explore this method in the preparation of PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Since starch is a biopolymer, its association with PBAT can even enhance environmental benefits. In fact, PBAT/starch blend has been used for the development of films with biodegradability and compostability properties, as an alternative to conventional non-biodegradable bags made of LDPE (Garcia et al, 2014(Garcia et al, , 2018Cardoso et al, 2018;Olivato et al, 2013Olivato et al, , 2014Brandelero et al, 2013;Nobrega et al, 2013).…”
Section: Introductionmentioning
confidence: 99%